Psychosocial Distress in Chronic Disease Patients in Salatiga - Muninggar, Jodelin; Sudarmi, Sudarmi; Setyaningrum, Juli (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Patients of hypertension (HT), diabetes mellitus (DM), and mixed (DM-HT) have a vulnerability to stress due to illness and psychosocial responses. Research aimed to identify psychosocial distress, the components, and their relationship to levels of GDP, systole/diastole, and cholesterol in three groups. The quantitative survey research was designed for 42 people, with purposive sampling at the Manunggal Clinic. The collection of psychosocial distress data was by a standard questionnaire. While systole/diastole, GDP, and cholesterol levels with an examination in the laboratory, in April-May 2018. Analysis with ANOVA and Pearson test, α0.05. Shows sufferers have low distress, moderate distress, and high distress. The average score of emotional component (3.2), chronic disease management difficulties (3.2), difficulties with doctors (3.0), and difficulties with friends/people around (2.6). ANOVA test showed no significant difference in psychosocial distress scores (p=0,079). The Pearson test showed a weak correlation between psychosocial distress and systole; diastole; GDP and cholesterol. Conclusion: Psychosocial distress of chronic disease sufferers in Salatiga is included in the category of moderate and high. The highest score on the emotional burden component and the difficulty of chronic disease management. There were no significant differences in psychosocial distress scores, blood pressure, blood sugar levels, and cholesterol in the three groups.